Examination of Methods for Limiting Interest: Systematic Literature Review - Alfandia, Nurlita Sukma (FIA UB, 2024)
The study employs a literature review. We acquired and deliberated over findings through online scholarly publications, news articles, and official guidelines. Most countries have implemented the Thin Capitalization Rule (TCR) to restrict interest deductions that exceed a certain debt threshold. Multiple nations employ the safe harbor rule, while others utilize earnings-stripping measures or employ both methods together. The Debt-to-Equity Ratio (DER) is the prevailing rule for thin capitalization worldwide. The OECD advocates for the enhancement of DER. The OECD does not support using DER as a TCR in the final report of BEPS Action 4. Instead, they recommend implementing restricted costs or income-stripping rules. The OECD recommends that countries establish a consistent baseline ratio of 10% to 30%. Many developed countries have implemented a 25-30% limitation on EBITDA, TAX EBITDA, or Adjusted Income. Malaysia and other developing nations limit interest deductions to a maximum of 20%. Indonesia has committed to transition from thin capitalization to earnings stripping restrictions, which aligns with BEPS Action Plan 4, which involves applying the net interest/EBITDA ratio. This commitment was made after the enactment of Tax Law Number 7 Year 2021, which aims to harmonize tax regulations. Meanwhile, Indonesia is actively addressing the issue.